Genetic polymorphisms of GGT1 gene (rs8135987, rs5751901 and rs2017869) are associated with neoadjuvant chemotherapy efficacy and toxicities in breast cancer patients - Lu Sun; Ziping Wu; Yanping Lin; Shuguang Xu; Yumei Ye; Wenjin Yin; Liheng Zhou; Jingsong Lu (BMC, 2023)
Abstract Background Our previous study illustrated the predictive value of serum gamma-glutamyl transpeptidase (GGT) for neoadjuvant chemotherapy (NAC) sensitivity in breast cancer patients. In this study we aim to determine whether single nucleotide polymorphisms (SNPs) in the gamma-glutamyltransferase 1 (GGT1) gene are related to the NAC response and adverse events and to find out a genetic marker in predicting NAC sensitivity. Methods Three SNP loci (rs8135987, rs5751901, rs2017869) of GGT1 gene were selected and tested among breast cancer patients reciving NAC. Four genotype models were used in SNP analysis: co-dominant model compared AA vs. Aa vs. aa; dominant model compared AA vs. Aa + aa; recessive model compared AA + Aa vs. aa; over-dominant model compared AA + aa vs. Aa. Chi-squared test and multivariable logistic regression analysis were performed between SNP genotypes, haplotypes and pathological complete response(pCR), adverse events as well as serum GGT level. Results A total of 143 patients were included in the study. For SNP rs8135987 (T > C), the TC genotype in over-dominant model was inversely related with pCR (adjusted OR = 0.30, 95% CI 0.10-0.88, p = 0.029) as well as the risk of peripheral neuropathy (adjusted OR = 0.39, 95% CI 0.15-0.96, p = 0.042). The TC genotype in dominant model was significantly associated with elevated serum GGT level (OR = 3.11, 95% CI 1.07-9.02, p = 0.036). For rs2017869 (G > C), the occurrence of grade 2 or greater neutropenia (OR = 0.39, 95% CI 0.08-0.84, p = 0.025) and leukopenia (OR = 0.24, 95% CI 0.08-0.78, p = 0.017) were both significantly reduced in patients with CC genotypes. For rs5751901(T > C), the CC genotype could significantly reduce the risk of grade 2 or greater neutropenia (OR = 0.29, 95% CI 0.09-0.96, p = 0.036) and leukopenia (OR = 0.27, 95% CI 0.09-0.84, p = 0.024) in recessive model. Conclusions The GGT1 gene SNPs might be an independent risk factor for poor response of NAC in breast cancer patients, providng theoretical basis for further precision therapy.